CHROMITE COMPOSITION AND PLATINUM-GROUP MINERAL ASSEMBLAGE IN THE UKTUS URALIAN-ALASKAN-TYPE COMPLEX (CENTRAL URALS, RUSSIA) - Garuti G.; Zaccarini F.; Pushkarev E.V.; Anikina E.; Cabella R. (My University, 2003)
Chromitite segregations in dunites of the Uktus Uralian-Alaskan-type complex (Central Urals, Russia) display large variation of the chromite composition: Cr/(Cr+Al)=0.46-0.77, Fe2+/(Fe2++Mg)=0.28-0.66, and Fe3+/(Fe3++Fe2+)=0.23-0.59. Three types of PGM assemblages have been recognized, varying in accordance with chromite composition: type I, dominated by Ru-Os-Ir (sulfides), is associated with magnesiochromite having Fe3+/(Fe3++Fe2+)<0.30, in the southern dunite body. Type II, containing abundant Pt-Ir (alloys, minor sulfides), is found in magnesiochromite with Fe3+/(Fe3++Fe2+)=0.40-0.44; type III, consisting of Ir-Rh-Pt-Pd (alloys, sulfarsenides, antimonides) in Fe-rich chromite having Fe2+/(Fe2++Mg)=0.66 and Fe3+/(Fe3++Fe2+)=0.59. Positive anomalies of Ir and Pt, and a negative peak of Ru characterize the PGE patterns of chromitites with type II and III PGM assemblages, whereas a positive Pt anomaly is observed in their dunite host. Intensive fractionation of Pt-Fe alloys in the Uktus chromitites reflects the anomalous behavior of Pt which is decoupled from Rh and Pd. Among other factors, the high iron activity and oxygen fugacity in the parent melt appear to exert a major control on precipitation of Pt-Fe alloys, below sulfur saturation. The strong Pt anomaly in chromitites from Uktus may indicate that Uralian-Alaskan-type magmas were derived from a Pt-rich mantle source.